2018
DOI: 10.1038/s41598-018-35306-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual variability in diving, movement and activity patterns of adult bearded seals in Svalbard, Norway

Abstract: Bearded seals are one of the least studied Arctic marine mammals, despite their circumpolar distribution and importance as a resource to Inuit communities. In this study, adult bearded seals (Erignathus barbatus) were equipped with GPS-Argos-CTD-SRDLs in Svalbard, Norway (2011–2012, n = 7) to document their diving, activity and movement patterns in a region where their habitat is changing rapidly. Five seals transmitted for > 8 months, sending 21,738 GPS-positions and 17,866 dives between July and April. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 84 publications
(103 reference statements)
3
19
1
Order By: Relevance
“…Svalbard's isolated location and its narrow shelf might be defining regional characteristics de termining these choices by this benthic-feeding seal species. Bearded seals of all ages are quite sedentary in Svalbard, largely remaining in shallow, coastal areas (this study, Gjertz et al 2000, Krafft et al 2000, Hamilton et al 2018. Similar to the pups in this study, adults were found in coastal areas with low sea-ice concentrations (″10%) in the summer and early autumn, and preferred intermediate sea-ice concentrations (10− 70%) in the late-autumn and winter, according to Hamilton et al (2018).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Svalbard's isolated location and its narrow shelf might be defining regional characteristics de termining these choices by this benthic-feeding seal species. Bearded seals of all ages are quite sedentary in Svalbard, largely remaining in shallow, coastal areas (this study, Gjertz et al 2000, Krafft et al 2000, Hamilton et al 2018. Similar to the pups in this study, adults were found in coastal areas with low sea-ice concentrations (″10%) in the summer and early autumn, and preferred intermediate sea-ice concentrations (10− 70%) in the late-autumn and winter, according to Hamilton et al (2018).…”
Section: Discussionsupporting
confidence: 70%
“…The number of pups transmitting data is shown above (a) lower total body oxygen stores of pups compared to adults do not provide a large constraint due to the large size of bearded seal pups and the fact that they forage on shallow-dwelling benthos (infauna, epifauna and benthically distributed fishes; Lowry et al 1980. Pups did dive to greater depths than adult bearded seals in Svalbard until they were 180 d old, when diving depths became shallower (this study, Hamilton et al 2018). Pups likely dove to deeper depths than adults in an ex ploratory manner, be fore they learned that food is found at shallow depths.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations